ANALISIS SEKTOR-SEKTOR EKONOMI DENGAN POTENSI UNGGULAN DI KABUPATEN/KOTA SE-PROVINSI JAWA TENGAH TAHUN 2000 – 2004 - Ahmad, Abdul Aziz (Jurnal Ekonomi & Studi Pembangunan, 2007)
Potential economic resources in the Central Java Province provide interesting features for analysis, especially agricultural sectors, where many regencies have relied on since 2000, but declined in 2004. Based on the State Location Quotient (LQ), this study finds the change in some leading economic sectors from 2002 to 2004 in those regencies and cities as well. The tendency of the change has an implication in the growth of the role in every single sector, relatively among the regions (regencies and cities). On the other hand, the Dynamic Location Quotient (ΔLQ) shows LQ variation across regions and some coincidence in decrease. If the decrease continuously occurs in important sectors of the regions with lower and negative LQ growth, there will also be adverse economic implications. In contrast, regions with higher and positive LQ growth will improve their potential economic resources.